2010
DOI: 10.1017/s0022029910000129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CSN1S1 genotype and its interaction with diet energy level on milk production and quality in Girgentana goats fed ad libitum

Abstract: A study was carried out to evaluate how the energy level of the diet can affect milk production and quality in Girgentana lactating goats in relation to polymorphism at the alphas1-casein (CSN1S1) genotype locus. Twenty-seven goats, homogeneous for milk production (1.5+/-0.3 kg/d), days of lactation (90+/-10 d) and body weight (35.8+/-5.5 kg) were selected on the basis of their CSN1S1 genotype, as follows: nine goats homozygous for strong (AA) alleles, nine goats homozygous for weak alleles (FF) and nine goats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
22
5
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 34 publications
15
22
5
1
Order By: Relevance
“…The DM and main nutrients intake were strongly influenced by diet, while it did not reveal a significant effect of CSN1S1 genotype and diet by genotype interaction ( Table 1). Similar results were found by Bonanno et al [29] and Pagano et al [10]. In particular, Bonanno et al [29] reported no difference in DM intake between goats with strong (aa) and heterozygous (aF) genotypes, like in the present study, although they observed a lower feed intake in goats with a weak (FF) genotype.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The DM and main nutrients intake were strongly influenced by diet, while it did not reveal a significant effect of CSN1S1 genotype and diet by genotype interaction ( Table 1). Similar results were found by Bonanno et al [29] and Pagano et al [10]. In particular, Bonanno et al [29] reported no difference in DM intake between goats with strong (aa) and heterozygous (aF) genotypes, like in the present study, although they observed a lower feed intake in goats with a weak (FF) genotype.…”
Section: Resultssupporting
confidence: 92%
“…Because feed also exerts a great influence on the yield and properties of goat milk, there is interest in how nutrition might interact with the genetic polymorphism at α S1 -Cn. Recent researches showed how aa goats, compared with FF goats, more efficiently utilize dietary protein [7][8][9] and respond to high-energy diets by utilizing nutrients more efficiently and achieving a higher milk yield [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this report, milk fat was not influenced by CSN1S1 genotype, in contrast with Pagano et al (2010) where high genotype goats showed a higher milk fat content than low genotype goats.…”
Section: Milk Yield and Compositioncontrasting
confidence: 84%
“…As these milk properties are also affected by nutrition, it is of some interest to consider the interaction of the CSN1S1 genotype and dietary characteristics. Few studies focusing on this aspect, demonstrated that strong alleles are related to a greater efficiency of protein utilization (De la Torre et al 2009), and to a better response to high dietary energy level compared to weak alleles (Pagano et al 2010). In order to contribute to the knowledge of the relationships between nutrition and CSN1S1 genotype in goats, this study was aimed to investigate the impact of fresh forage based diet and/or energy supplement on feeding behaviour, milk production, metabolic and hormonal parameters and oxidative stress of Girgentana goats with different genotype at CSN1S1 locus.…”
Section: Resultsmentioning
confidence: 99%